Cracking sletv mysteries: Enhancing 8th graders problem-solving abilities through polya’s approach, reviewed by initial math proficiency - Maria Megawati Putri; Muhamad Toyib (Universitas Islam Negeri Raden Intan Lampung, 2025)
Despite the importance of problem-solving skills in mathematics, many students struggle due to conventional teaching methods that do not consider differences in initial abilities. This study addresses this gap by examining the effectiveness of the Polya problem-solving approach on eighth-grade students’ mathematical problem-solving skills. A quasi-experimental design was conducted at MTs Negeri 1 Wonogiri in the 2024/2025 academic year, with class VIII A2 as the experimental group (Polya approach) and class VIII A1 as the control group (conventional approach). Students’ performance was assessed using a validated test on Two-Variable Linear Equation Systems. Data analysis using two-way ANOVA showed that students in the Polya group achieved an average score of 83.42, higher than the control group (71.24). Initial ability significantly influenced outcomes (high: 96.56, medium: 78.28, low: 63.63), and a significant interaction was observed between teaching method and initial ability, indicating that Polya’s approach benefits students across all ability levels. These results highlight the importance of structured problem-solving methods in improving mathematics learning outcomes.